Length weight relationship and otolith morphometry of twelve species of sciaenids (Family: Sciaenidae) from Mumbai waters, India - Kumar, Pawan; Chakraborty, S. K.; Jaiswar, A. K.; Ali, Shahnawaz (Indian Journal of Fisheries, 2015)
Length-weight relationship of 12 fish species belonging to the family Sciaenidae landed at New Ferry Wharf, Sassoon Dock and Versova fish landing centers of Greater Mumbai were estimated between September 2006 and August 2007. A normal distribution of calculated ‘b’ values ranged from 2.3585 to 3.5458 and r2 values of length-weight relationship varied from 0.6356 to 0.9886. The Student’s t-test revealed that the b values significantly differed in 7 of the 12 species studied (p<0.05). Morphometric relationship between otolith dimensions and fish weight were also studied. The significance of parameters like otolith length, width and mass was correlated for estimation of fish weight employing multiple regression model. ANCOVA test indicated that difference between left and right sagitta in otolith length, width and mass were insignificant (t-test, p<0.05). Results also indicated better correlation between fish weight and otolith measurement. Analysis of morphometric relationships concluded that otolith length, width and mass are good indicators of total length and weight in the species studied.